Burnout syndrome and coping strategies among therapeutic attendants - Reyna, Cecilia (2011)
The purpose of this study was to analyze the manifestations of Burnout syndrome in a particular group of health workers, therapeutic attendants. In addition, coping strategies are studied, both in general terms and specific strategies of the profession, and its relationship with symptoms of the syndrome. The sample consisted of 17 professionals from Córdoba (Argentina) of both sexes (41.2% males), aged between 22 and 53 years (M=29.53 years,SD=7.43). The prevalence of different symptoms of the syndrome is discussed considering different criteria of cut, with mixed results; while relations with the coping strategies were only evident among some dimension.